New observations on the Brazilian Merganser - Bartmann, Wolf (Wildfowl, 1988)
Preliminary observations in 1981-83 revealed and confirmed the occurrence of the Brazilian Merganser Mergus octocetaceus endemic in the area of Serra da Canastra National Park in Minas Gerais, south-eastern Brazil. In 1984 a breeding pair rearing six chicks was found here and observed closely during the middle of August. The adult pair remained strongly bonded and the male took part in parental care. Day-time activities and behaviour are described. The species is a year-round resident and territorial in that area. The species should be secure here, as long as the appropriate habitat is not violated.